Physical activity and its correlation with various measures of obesity among medical students and young faculty - Bhavna Pramod Joshi; Swati Manikrao Mahajan; Deepak Narayan Tayade (Elsevier, 2023)
Background: Physical inactivity is important modifiable risk factor for major NCDs. Medical students and faculty who are physically active are more probable to prescribe physical activity to their patients, drastically improving clinical outcomes. Objectives: 1) To describe physical activity of participants in terms of pattern, type & levels. 2) To correlate physical activity with various measures of obesity. Methods: This cross-sectional study was conducted among 350 medical students and young faculty aged 18-35 years. Physical activity was assessed using WHO GPAQ. Physical activity pattern was described in work, travel and leisure domains. It was classified into vigorous and moderate intensity activity types. Levels were defined as insufficiently, moderately and highly active. Measurement of various obesity parameters was done. Data was analyzed using SPSS v25.0. Results: Of all respondents, 193 (55.14%) were males and 157 (44.86%) were females. The prevalence of insufficient physical activity was 20.57%. Respondents reported highest physical activity in leisure domain (1222.45 ± 1590.8 mean METM/W). BMI was significantly correlated with physical activity in transport (p = 0.018) and leisure (p < 0.0001) domains. Neck circumference was significantly correlated with physical activity in transport (p = 0.018) and leisure (p < 0.0001) domains. Waist circumference was significantly correlated with physical activity in leisure domain (p < 0.0001).Waist circumference (p = 0.036) and neck circumference (p = 0.004) were significantly correlated with levels of physical activity. Total 327 (93.42%) respondents reported sedentary time >6 h/day. Conclusion: This population needs to adopt changes in their lifestyle to increase physical activity especially in travel domain with reduction in sedentary time.